Induction of Systemic Resistance in Hibiscus sabdariffa Linn. to Control Root Rot and Wilt Diseases Using Biotic and Abiotic Inducers - Hamada F. A. Ahmed; Sameh Elnaggar; Gomaa A. Abdel-Wahed; Ragab S. Taha; Awais Ahmad; Wadei A. Al-Selwey; Hoda M. H. Ahmed; Naeem Khan; Mahmoud F. Seleiman (Biology, 2023)
The possibility of inducing systemic resistance in roselle against root rot and wilt diseases was investigated using biotic and abiotic inducers. The biotic inducers included three biocontrol agents (i.e., Bacillus subtilis, Gliocladium catenulatum, and Trichoderma asperellum) and two biofertilizers (i.e., microbein and mycorrhizeen), while the abiotic inducers included three chemical materials (i.e., ascorbic acid, potassium silicate, and salicylic acid). In addition, preliminary in vitro studies were conducted to evaluate the inhibitory activity of the tested inducers on the growth of pathogenic fungi. The results show that G. catenulatum was the most efficient biocontrol agent. It reduced the linear growth of Fusarium solani, F. oxysporum, and Macrophomina phaseolina by 76.1, 73.4, and 73.2%, respectively, followed by B. subtilis by 71.4, 69, and 68.3%, respectively. Similarly, potassium silicate was the most effective chemical inducer followed by salicylic acid, each at 2000 ppm. They reduced the linear growth of F. solani by 62.3 and 55.7%; M. phaseolina by 60.7 and 53.1%; and F. oxysporum by 60.3 and 53%, respectively. In the greenhouse, all inducers applied as a seed treatment and/or foliar spray strongly limited the development of root rot and wilt diseases. In this regard, G. catenulatum, at 1 × 109 CFU mL−1, achieved the highest values of disease control, followed by B. subtilis; while T. asperellum, at 1 × 105 CFU mL−1, recorded the lowest values. In addition, the plants treated with potassium silicate followed by salicylic acid, each at 4 g/L, recorded the highest disease control compared to ascorbic acid at 1 g/L, which had the lowest values. The mixture of mycorrhizeen + microbein (at 10 g/kg seeds) was the most effective compared to either of them alone. All treatments, applied alone or in combination in the field, significantly reduced the incidence of diseases. The most effective treatments were a mixture of G. catenulatum (Gc) + Bacillus subtilis (Bs) + Trichoderma asperellum (Ta); a mixture of ascorbic acid (AA) + potassium silicate (PS) + and salicylic (SA); G. catenulatum; potassium silicate; and a mixture of mycorrhizeen + microbein. Rhizolix T had the highest disease-reducing efficacy. In response to the treatments, significant improvements in growth and yield, changes in biochemicals, and increased activities of defense enzymes were achieved. This research points to the activity of some biotic and abiotic inducers that can play a vital role in managing the root rot and wilt of roselle through the induction of systemic plant resistance.